Workshop Stamps on Italic Terra Sigillata from Zaton near Zadar (Archaeologia Adriatica, 2022)
The paper deals with some of the archaeological finds collected in the systematic underwater excavations of the ancient port in Zaton at Cape Kremenjača, conducted by the Department of Underwater Archaeology of the Archaeological Museum in Zadar. The excavations were organized intermittently from the late 1960s to 2019. In this long-term research, the port yielded a number of diverse archaeological finds and the remains of three sewn-plank boats, as well as the breakwater remains. Analyzed pottery comprises fragments of various types of Italic and northern Italic sigillata production bearing workshop stamps, recovered in the excavations from the late 1960s to 2012. Examination of the workshop stamps found on the seabed of Zaton resulted in a list of known workshop stamps on 39 plate sherds and 38 cup sherds, as well as some hitherto unknown types, with photographs and outlines arranged in tables by vessel types. Northern Italic workshops are dominant among analyzed vessels, though unidentified workshops are actually most numerous. The workshop with the stamp M. S. MOSCHVS produced most examples in the assemblage.
Keywords: antiquity; Zaton; terra sigillata; stamps